Effect of the technological parameters of plasma-arc spraying of flux-cored wire on the structure and properties of intermetallide coatings based on Fe3Al - Korzhyk, Volodymyr; Burlachenko, Oleksii; Strohonov, Dmytro; Fialko, Nataliia; Kharlamov, Maksym; Grishchenko, Oleksandr; Peleshenko, Sviatoslav (Eastern-European Journal of Enterprise Technologies, 2023)
Existing techniques for applying intermetallide layers are characterized by low productivity, difficulties associated with the maintenance and operation of technological equipment, as well as significant costs for the purchase of materials for spraying. Therefore, modern science shows considerable interest in the development of new, highly effective technologies to form intermetallide coatings on the surface of articles. Such promising techniques include the technology of plasma-arc spraying (PAS) of flux-cored wires. This technique has a number of significant advantages, namely high performance, relative simplicity, as well as the affordability of equipment and materials for coating. This paper reports a study into the structure and properties of coatings obtained by flux-cored wire PAS, in which the steel sheath and aluminum powder filler interact when heated with the exothermic effect of Fe3Al synthesis. The influence of technological parameters of PAS process on the structure and properties of Fe-Al coatings was investigated by means of mathematical planning of the experiment. It was found that in all samples the main phase is an intermetallide of the Fe3Al type. Tests for gas-abrasive wear resistance at room temperature showed that the wear resistance of coatings exceeds the stability of steel S235 by an average of 2 times. As a result of studying the electrochemical properties in a 3-% aqueous solution of NaCl and in a 0.5-% solution of H2SO4, the score of corrosion resistance for these media was determined, which was, respectively, 4 and 5 (coatings belong to the group of "resistant"). In this regard, the practical use of coatings based on the Fe3Al intermetallide is recommended for protection against oxidation, corrosion, and gas-abrasive wear of components and assemblies in the heat power industry (heat exchanger pipes, catalytic converters, steam turbine blades, shut-off valves, etc.)